Folk stories and personal narratives in Palestinian spoken Arabic : a cultural and linguistic study - Sirhan, Nadia R.; SpringerLink (Online service). (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
By analysing the folk stories and personal narratives of a cross-section of Palestinians, Sirhan offers a detailed study of how content and sociolinguistic variables affect a narrator's language use and linguistic behaviour. This book will be of interest to anyone engaged with narrative discourse, gender discourse, Arabic studies and linguistics.
Keywords: Linguistics; Ethnology; Sociolinguistics; Discourse analysis; Cultural studies; Linguistics; Discourse Analysis; Sociolinguistics; Cultural Anthropology; Cultural Studies